Bochdalek hernia in an adult: two case reports and a review of perioperative cardiopulmonary complications - Masayuki Akita; Nobuaki Yamasaki; Taiichiro Miyake; Kazuya Mimura; Eri Maeda; Tohru Nishimura; Koichiro Abe; Akihito Kozuki; Kunio Yokoyama; Hiroaki Kominami; Tomohiro Tanaka; Manabu Takamatsu; et al. (Surgical Case Reports)
Abstract Background Bochdalek hernia in an adult is very rare and often needs an immediate surgical repair for the herniation. Although its etiology and surgical techniques have frequently been reported, perioperative complications, especially cardiopulmonary problems, remain unknown. We reported two adults with Bochdalek hernia and reviewed the published literatures with a focus on these issues. Case presentation We experienced two adult cases of Bochdalek hernia with gastrointestinal strangulation. One case had massive herniation of the stomach, colon, spleen, and pancreas in the left chest, causing repeated vomiting. The other had a right-side hernia with strangulation of the colon. We successfully performed emergency repairs of these diaphragmatic hernias without any postoperative complications. Conclusions Our literature review revealed that life-threatening cardiopulmonary complications, such as empyema or cardiac arrest caused by the tamponade effect of the herniated viscera, sometimes occurred in patients with Bochdalek hernia. These complications were found in Bochdalek hernia with gastrointestinal strangulation.